Sistem Otomatisasi Pakan Ikan Lele dan Pemantauan Kualitas Air Menggunakan Platform Arduino - Lailatul Husna Lubis; Mulkan Iskandar Nasution; Shiti Indriani (Universitas Negeri Medan, 2026)
The Arduino-based aquaponics automation control system for catfish farming is designed to optimize catfish rearing in urban environments by using various sensors and automation components. This system utilizes a pH sensor, temperature sensor, and TDS sensor to monitor water quality in real-time, as well as an ultrasonic sensor to measure the water level in the pool. Data from these sensors is used to regulate and control the water pump system, which functions as a means of recirculating water to keep it clean and maintain its quality. With the results, the TDS sensor value has a range of 327.75 – 325.22 ppm. The pH sensor value has a range of 7.09 – 7.05. The temperature sensor value has a range of 29.94 – 30.00 ℃. The value of the ultrasonic sensor by measuring the water level of the fish pond with a value obtained is 28 cm. Apart from that, this system is equipped with a servo motor which is used to feed the fish automatically, ensuring that the fish get food on time, feeding once a day at 17:00 WIB with a total feed output of 188 gr for 5 seconds with the servo angle being 90°. All data generated from these sensors is stored in a structured manner in memory for long-term analysis and monitoring purposes. Implementation of this control system shows effective results in raising catfish in urban settlements. With automation and continuous monitoring, this system not only simplifies aquaponics management but also increases efficiency and sustainability in dense urban environments. This system offers a practical and innovative solution to the problem of maintaining aquaponics in limited areas, as well as contributing to the development of sustainable urban farming technology